A clean sightline to quiescence: multiwavelength observations of the high Galactic latitude black hole X-ray binary Swift J1357.2-0933 - Plotkin, Richard; Gallo, E.; Jonker, P.; Miller-Jones, James; Homan, J.; Munoz-Darias, T.; Markoff, S.; Padilla, M.; Fender, R.; Rushton, A.; Russell, D.; Torres, M. (Oxford University Press, 2016)
We present coordinated multiwavelength observations of the high Galactic latitude (b = +50°) black hole X-ray binary (BHXB) Swift J1357.2−0933 in quiescence. Our broad-band spectrum includes strictly simultaneous radio and X-ray observations, and near-infrared, optical, and ultraviolet data taken 1–2 d later. We detect Swift J1357.2−0933 at all wavebands except for the radio (f5 GHz < 3.9 μJy beam−1; 3σrms). Given current constraints on the distance (2.3–6.3 kpc), its 0.5–10 keV X-ray flux corresponds to an Eddington ratio LX/LEdd = 4 × 10−9–3 × 10−8 (assuming a black hole mass of 10 M⊙). The broad-band spectrum is dominated by synchrotron radiation from a relativistic population of outflowing thermal electrons, which we argue to be a common signature of short-period quiescent BHXBs. Furthermore, we identify the frequency where the synchrotron radiation transitions from optically thick-to-thin (νb ≈ 2–5 × 1014 Hz), which is the most robust determination of a ‘jet break’ for a quiescent BHXB to date. Our interpretation relies on the presence of steep curvature in the ultraviolet spectrum, a frequency window made observable by the low amount of interstellar absorption along the line of sight. High Galactic latitude systems like Swift J1357.2−0933 with clean ultraviolet sightlines are crucial for understanding black hole accretion at low luminosities.